Bone Bruise and Anterior Cruciate Ligament Tears: Presence, Distribution Pattern, and Associated Lesions in the Pediatric Population. Issue 13 (November 2019) - Bordoni, Vittorio; di Laura Frattura, Giorgio; Previtali, Davide; Tamborini, Simone; Candrian, Christian; Cristallo Lacalamita, Marirosa; Del Grande, Filippo; Filardo, Giuseppe
Background: Bone bruise characteristics after anterior cruciate ligament (ACL) injury have been correlated with the level of joint derangement in adults. However, the literature lacks information about younger patients, whose higher ligamentous laxity may lead to different lesion patterns. Purpose: To investigate the prevalence, size, location, and role of bone bruise associated with ACL rupture in the pediatric population. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Knee magnetic resonance imaging scans (MRIs) of patients aged 8 to 16 years with ACL tears from 2010 to 2018 were selected from the institution database. Inclusion criteria were open or partially open physes, less than 90 days between trauma and MRI, and no history of injury or surgery. Presence, localization, and size of bone bruise were analyzed by 2 blinded researchers and scored with the Whole-Organ Magnetic Resonance Imaging Score (WORMS) bone bruise subscale. Ligamentous, cartilaginous, meniscal, and other lesions were documented. Results: Of the 78 pediatric patients selected from the database, 54 (69%) had bone bruise. The mean area of bone bruise was larger in males than in females (femur, 3.8 ± 2.8 vs 2.2 ± 1.4 cm 2, respectively, P = .006; tibia, 2.6 ± 1.6 vs 1.5 ± 0.8 cm 2, respectively, P = .007). The subregions most affected by bone bruise were the lateral posterior tibia and the lateral central femur (in 83% and 80% of the knees affected, respectively). A low correlation was found between age and bone bruise area (biggest areas r = 0.30, P = .03, and sum of areas r = 0.27, P = .04), but no correlation was found between age and WORMS (femur, r = −0.03, P = .85; tibia, r = −0.04, P = .76). The injuries most associated with bone bruise were 23 meniscal lesions (43%), 10 lesions of other ligaments (19.0%), 2 cartilage lesions (3.7%), and 2 patellar fractures (3.7%). Conclusion: The prevalence of bone bruises in pediatric patients with ACL tears is high, although it seems slightly lower than the prevalence documented in adults but with similar localization. The area and the distribution pattern of bone bruises are similar among different ages. The pediatric patients had a lower presence of cartilage and meniscal lesions compared with that reported in adults, which suggests a different effect of this trauma on the knee of pediatric patients.